The persistent effects of regional policy - Evidence from the West-German Zonenrandgebiet. - Ehrlich, Maximilian von; Seidel, Tobias (My University, 2014)
In this paper, we provide novel evidence on the contemporaneous and persistent effects of regional policy. We apply a quasi-experimental identification strategy exploiting the fact that municipalities in the West-German Zonenrandgebiet (ZRG) were eligible for substantial regional transfers between 1971 and 1994. The ZRG was an approximately 40km-band adjacent to the Iron Curtain during the Cold War in West Germany. Apart from determining transfer eligibility, this pure geographic threshold did not have any institutional, cultural or economic relevance. We use regression discontinuity to estimate the causal effects of regional policy on economic activity. Using disaggregated data on the municipality level and satellite night light data (as a proxy for GDP), we find that the ZRG treatment led to an increase of income per square kilometer of about 50 percent in 1986. Importantly, economic density remained high in 2010 although the transfers had phased out in 1994. This speaks against unique equilibria determined by locational advantage, but rather strengthens market externalities as an important explanation for the spatial distribution of economic activity. We also examine several potential channels finding strong contemporaneous and persistent effects of transfers on population density and the business tax base.
Keywords: Wirtschaftspolitik; Regionalpolitik; Wirtschaftsentwicklung; Standortentwicklung